Mengungkap Makna Pendapatan dalam Perspektif Sopir Bus di Masa Pandemi Covid-19 - Ihda Izzatul Alfaini; Mochammad Ilyas Junjunan; Ajeng Tita Nawangsari (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to understand in depth the meaning of income according to the perspective of city transportation bus drivers at the Paciran terminal during the COVID-19 pandemic. In this study, the meaning of income is formed by the environment of the city transport bus drivers.Method: This study uses the approach with the interpretive paradigm of Husserl's transcendental phenomenology. The phenomenological method emphasizes the meaning that arises from each individual's experience and awareness. Results: The results showed that the informants had different meanings of income. Income is interpreted as a form of material used to meet family needs and future savings. Income is a non-material form, namely the income of inner satisfaction by feeling happy because it helps passengers who need transportation, and income is a spiritual form by applying